Tri-Band Regulation and Split-Type Smart Photovoltaic Windows for Thermal Modulation of Energy-Saving Buildings in All-Season - Wang, Qian; Na, Zongxu; Gao, Jianfei; Yu, Li; Chen, Yuanwei; Gao, Peng; Ding, Yong; Dai, Songyuan; Nazeeruddin, Mohammad Khaja; Yang, Huai (Nano-Micro Letters, 2026)
Energy-saving buildings (ESBs) are an emerging green technology that can significantly reduce building-associated cooling and heating energy consumption, catering to the desire for carbon neutrality and sustainable development of society. Smart photovoltaic windows (SPWs) offer a promising platform for designing ESBs because they present the capability to regulate and harness solar energy. With frequent outbreaks of extreme weather all over the world, the achievement of exceptional energy-saving effect under different weather conditions is an inevitable trend for the development of ESBs but is hardly achieved via existing SPWs. Here, we substantially reduce the driving voltage of polymer-dispersed liquid crystals (PDLCs) by 28.1 % via molecular engineering while maintaining their high solar transmittance (Tsol = 83.8 %, transparent state) and solar modulating ability (ΔTsol = 80.5 %). By the assembly of perovskite solar cell and a broadband thermal-managing unit encompassing the electrical-responsive PDLCs, transparent high-emissivity SiO2 passive radiation-cooling, and Ag low-emissivity layers possesses, we present a tri-band regulation and split-type SPW possessing superb energy-saving effect in all-season. The perovskite solar cell can produce the electric power to stimulate the electrical-responsive behavior of the PDLCs, endowing the SPWs zero-energy input solar energy regulating characteristic, and compensate the daily energy consumption needed for ESBs. Moreover, the scalable manufacturing technology holds a great potential for the real-world applications. Highlights: 1 Broadening the modulation range and decreasing the driving voltage of polymer dispersed liquid crystals via molecular engineering without sacrificing high solar transmittance (transparent state) and solar modulating ability. 2 Modulating capability of the smart photovoltaic windows across visible, near-infrared and mid-infrared bands enabling superb energy-saving performance in all season. 3 Holding a great potential for real-world application due to their scalable manufacturing technology.